Design and Dynamic Analysis of a Novel Biomimetic Robotics Hip Joint - Bingyan Cui; Liwen Chen; Zhijun Wang; Yuanhao Zhao; Zhanxian Li; Zhenlin Jin (Applied Bionics and Biomechanics, 2015)
In order to increase the workspace and the carrying capacity of biomimetic robotics hip joint, a novel biomimetic robotics hip joint was developed. The biomimetic robotics hip joint is mainly composed of a moving platform, frame, and 3-RRR orthogonal spherical parallel mechanism branched chains, and has the characteristics of compact structure, large bearing capacity, high positioning accuracy, and good controllability. The functions of the biomimetic robotics hip joint are introduced, such as the technical parameters, the structure and the driving mode. The biomimetic robotics hip joint model of the robot is established, the kinematics equation is described, and then the dynamics are analyzed and simulated with ADAMS software. The proposed analysis methodology can be provided a theoretical base for biomimetic robotics hip joint of the servo motor selection and structural design. The designed hip joint can be applied in serial and parallel robots or any other mechanisms.